Investigating the Nucleation, Growth, and Energy Levels of Organic Semiconductors for High Performance Plastic Electronics - Virkar, Ajay.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This thesis details the progress made in improving the performance of organic transistors and the network conductivity of carbon nanotubes. The first section investigates organic semiconductor nucleation and growth on the most common dielectric surface used to fabricate organic thin film transistors. In the final section, lessons learned from studying organic semiconductor nucleation and growth were utilized to improve the conductivity of carbon nanotube networks. Selective nucleation of materials at the junctions between nanotubes in the network significantly decreased the network's sheet resistance. The resulting networks may be promising candidates for transparent electrodes with a variety of optoelectronic applications.
Introduction to Organic Semiconductors, Transistors and Conductors -- Organic Semiconductor Growth and Transistor Performance as a Function of the Density of the Octadecylsilane Dielectric Modification Layer -- The Nucleation, Surface Energetics and Stability of Pentacene Thin Films on Crystalline and Amorphous Octadecylsilane Surface -- Technological Importance of Crystalline Octadecylsilane Monolayers: Crystalline Monolayers Fabricated by Spin-Casting -- Alkylsilane Dielectric Modification Layer: Molecular Length Dependence and the Odd-Even Effect -- Low-Voltage Monolayer Pentacene Transistors Fabricated on Ultrathin Crystaline Self-Assembled Monolayer based Dielectric -- Highly Conductivity and Transparent Carbon-Nanotube and Organic Semiconductor Hybrid Films: Exploiting Organic Semiconductor Energy Levels and Growth Mode -- Outlook/Conclusions.
Keywords: Biochemical engineering; Semiconductors; Chemical engineering; Biochemical Engineering; Semiconductors; Industrial Chemistry/Chemical Engineering